Psychological impact of COVID-19 among health care workers working in a tertiary care hospital of South India: a cross-sectional study - Nelson, Vincy; Joy, Jomon; Stephen, Sabu (International Journal Of Community Medicine And Public Health, 2022)
Background: This study aimed to find out the psychological impact faced by the health care workers in a tertiary care hospital of India which will help in generalizing it to other states of the country as well other countries. Methods: A cross-sectional study was conducted in a tertiary care hospital of South Kerala. Study period was from July 2020 to August 2020 during the post lockdown period. Study participants included the staff nurses, interns, post graduate students, doctors, pharmacists, supporting staff. A pre-designed, semi-structured questionnaire was administered to the study subjects. The general health questionnaire (GHQ 12) questionnaire was used to find out the mental health of the participants. Results: A total of 200 subjects were included in the study among them 81 (40.5%) were males and 119 (59.5%) were females. Out of 200, doctors 148 (74%), nurses 36 (18%), pharmacist 6 (3%),supporting staff 10 (5%).Mean age of the population was 30.63±7.32 years. A GHQ-12 model questionnaire was used to assess the psychological distress among health care workers. In our study, the average GHQ-12 was 3.48 which was higher than the cut-off. Conclusions: COVID-19 has led to lot of mental health problems and the impact is very huge among health care workers. Main concerns were anxiety, burnout, depression, stress-related disorders, over work, concern about family members and so on. Policies should be made in the international and national levels to help health care workers manage pandemic in the coming days with less stress and anxiety.